THE APPLICATION OF KINDLING STRATEGY TO TEACHING READING OF VOCATIONAL HIGH SCHOOL 3 PAYAKUMBUH - Ifna Nifriza (Journal of Education, Linguistics, Literature and Language Teaching, 2022)
The study aims to know whether or not the application of kindling strategy is effective to improve students’ reading skill at the tenth grader of SMK. The population of this study was 538 students with the number of sample 40 students in class X.1. The research was experimental research in which only one class which was treated using the technique. The research instrument was reading test. the test was valid because it had content validity. To answer the hypothesis the data was scored by using T-test formula to see whether not the application of Kindling strategy gives significant effect in reading.